Pengaruh Pengelolaan Lahan dan Pemberian Pupuk Kandang Ayam terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Elda Sari Siregar (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
The purpose of this study was to determine the growth and production response of Shallots (Allium ascalonicum L.) to the types of mulch and chicken manure. This research was conducted at the location of Batang Ayumi Julu Village, Padangsidimpuan City. The experimental design used in this study was a factorial Randomized Block Design (RCBD), with two factors, namely the treatment of mulch (without mulch, silver black plastic mulch, rice straw mulch). Factors Provision of chicken manure (control, 1 kg / plot, 2 kg / plot, 3 kg / plot). The results showed that the treatment of mulch gave no significant effect on plant height parameters, the number of tillers, tuber weight per sample and tuber weight per plot. The treatment of giving chicken coop fertilizer also had no significant effect on the parameters of plant height, number of tillers, tuber weight per sample and tuber weight per plot. The interaction between the two treatments also gave no significant effect on the parameters of plant height, number of leaves, number of tillers, tuber weight per sample, tuber weight per plot. Keywords: mulch, shallots, chicken manure, production.